Education in Scotland - Clark, Margaret; Munn, Pamela (Taylor & Francis, 1998)
Education in Scotland is markedly different from what happens in the rest of the UK - with a different National Curriculum, school boards to oversee school management and a General Teaching Council which has been in existence since 1965. Whilst there are many examples of successful and innovative practice in Scotland, the system is quite often not recognised as different by writers who talk about the UK education system as if it were one smooth whole. This book describes recent developments in both legislation and practice in Scotland, drawing comparisons with the Eng system. Chapters cover: * administration and management * the professional competence of teachers * early years education provision * the 'National Curriculum' in Scotland * Secondary Education * Special Educational Needs